Vascular complications of infective endocarditis in Burkina Faso - Nobila Valentin Yameogo; S Jean Baptiste Tougouma; Larissa Justine Kagambega; Ismaël Diallo; Georges Rosario Christian Millogo; Koudougou Jonas Kologo; Andre K Samadoulougou; Patrice Zabsonré (Journal of Cardiovascular Medicine and Cardiology - Peertechz Publications, 2018)
Introduction: Vascular complications of infective endocarditis are frequent and severe. The aim of this study was to clarify the epidemiological, clinical and prognostic characteristics of these vascular damages and determine their associated factors. Patients and methods: We performed a descriptive cross-sectional study from 1 January 2013 to 31 December 2016 on patients admitted to the cardiology department of Yalgado Ouedraogo teaching Hospital for infective endocarditis and vascular complications recorded. The diagnosis of infective endocarditis was established on the basis of modified Dukef. Results: We recorded a total of 44 infective endocarditis. Vascular complications were found in 10 cases (22.7%) including 6 women and 4 men. The average age of patients was 36.7 years with extremes of 23 and 74 years. In total, seventeen vascular complications were recorded. They were dominated by neurological (7 cases) and acute limb ischemia (4 cases). The average time between the installation of the fever and the occurrence of vascular complications was 41.6 ± 6.5 days. Factors associated with embolization were reaching the mitral valve (RR = 2.5, p = 0.047), infection by Staphylococcus aureus (RR = 1.8, p = 0.022), the size of the upper vegetation 10 mm (RR = 1.8, p = 0.046), the mobility of the vegetation (RR = 1.5, p = 0.048) and late turning on appropriate antibiotics (dual antibiotic beyond 2 weeks after the start of fever) (RR = 1.4; p = 0.038). Mortality was heavy (60%) and neurological involvement was a poor prognostic factor. Conclusion: Vascular complications are frequent in infective endocarditis and are dominated by neurovascular damage. The factors associated with these complications are related to the characteristics of endocarditis. Neurological involvement is a poor prognostic factor.